Pengaruh Yoga Excercise Dalam Mempercepat Penurunan Kepala Janin Pada Ibu Hamil Trimester III - syifa, naufal; Norif Didik Nur Imanah; Rantauni, Dahlia Arief; Aksari, Septi Tri (An-Najat, 2025)
The third trimester of pregnancy is a critical period in preparing for childbirth, one of which involves facilitating the descent of the fetal head into the pelvic cavity. Fetal head descent is an indicator of labor readiness and can be supported through non-pharmacological interventions such as yoga exercises. This study aims to determine the effect of yoga exercises on accelerating fetal head descent in third-trimester pregnant women. The research employed a qualitative method with a case study approach on a single subject, Mrs. A, 22 years old, G1P0A0, with a gestational age of 41 weeks and a fetal head descent of 4/5. The intervention consisted of prenatal yoga performed daily for six consecutive days, each session lasting 30 minutes. The evaluation results showed a fetal head descent from 4/5 to 2/5 following the yoga sessions. The yoga exercises included a combination of stretching, breathing techniques, and relaxation designed to improve pelvic muscle flexibility and optimize fetal positioning. These findings indicate that yoga exercises are effective in accelerating fetal head descent before labor and can serve as a safe, non-pharmacological management alternative that is simple to implement.